Congenital heart disease in newborn children living at high altitude in China: a prospective study. (December 2017) - Li, Jing-Jing; Liu, Yuan; Xie, Si-Yuan; Zhao, Guo-Dong; Dai, Ting; Chen, Hong; Qi, Hai-Ying; Li, Jia
Abstract: Background: Screening newborn children for congenital heart disease (CHD) mostly focus on critical CHD using pulse oximetry. But this approach is not applicable to residents at high altitude because of variations in decreased arterial saturations. Altitude hypoxia induces pulmonary hypertension that is the main morbidity in simple left to right shunt forms of CHD. We aimed to screen newborn children at high altitude for all forms of CHD using echocardiography. Methods: We included asymptomatic newborn children born in Xining, Qinghai (2260 m) between March 1, 2015, and Aug 31, 2016. Echocardiography was done on days 3–5 after birth, and follow-up echocardiography was done at 3 months, 6 months, and 12–18 months. Informed consent was obtained from the parents of each neonate. As part of a quality initiative, the study did not require approval from the Institutional Ethics Board. Consent was obtained from the parent or parents of each neonate by verbal explanations. Findings: Echocardiography was performed in consecutive asymptomatic 1002 newborn children (459 girls, 543 boys; 219 Han, 673 Hui, 110 Tibetan; altitude 1800–4223 m, median 2450 m). CHD was detected in 278 (28%) children (139 girls, 139 boys; 67 Han, 181 Hui, and 30 Tibetan). Among the children with CHD, 176 children (63%) had secundumatrial septal defect, 61 children (22%) had patent ductus arteriosus, seven children (3%) had ventricular septal defect, and 34 children (12%) had multiple defects. 91 (33%) of the 278 children with CHD had a follow-up at 3 months: in eight (12%) of 69 children, the atrial septal defect had closed, and in 26 (87%) of 30 children the patent ductus arteriosus had closed. A 6 month follow-up was completed in 65 (26%) of 255 children; the atrial septal defect had closed in 28 (19%) of 57 children, the patent ductus arteriosus had closed in 11 (79%) of 14 children, and the ventricular septal defect had closed in two (67%) of three children. A 12–18 month follow up was completed in 59 (27%) of 223 children. Atrial septal defects, patent ductus arteriosus, and ventricular septal defects had closed in 23 (50%) of 46 children, 17 (85%) of 20 children, and three (75%) of four children, respectively. During the follow-up period, two babies with multiple defects died of pneumonia at 4 months and 6 months. Another two babies with atrial septal defect and one baby with patent ductus arteriosus had pulmonary arterial hypertension (systolic pressure 54 mm Hg and 50 mm Hg) at 12 months. In total, among the 166 (60%) children with CHD who attended follow-ups, defects remained unclosed in 99 (60%) children. The incidence of CHD and spontaneous closure were not correlated with altitudes and ethnic group (p>0·1 for all). Interpretation: The incidence of CHD is many fold higher than that at low altitude, consisting solely of simple left to right shunt forms. By 18 months of age, about 60% of CHD remain unclosed. Follow-up remains challenging because of poor socioeconomic conditions but must be reinforced to provide early repair and prevent pulmonary arterial hypertension and death. Funding: Start-up fund provided by the Capital Institute of Pediatrics.